STUDY OF SELECTIVE HYDROGEN SULFIDE ABSORPTION BY COMPARING TWO DIFFERENT ALKALI ABSORBENTS BY USINSTUDY OF SELECTIVE HYDROGEN SULFIDE ABSORPTION BY COMPARING TWO DIFFERENT ALKALI ABSORBENTS BY USING ATOMIZATION METHODG ATOMIZATION METHOD - MOLNÁR, Éva; RIPPEL-PETHŐ, Dóra; HORVÁTH, Géza; BOBEK-NAGY, Janka; BOCSI, Róbert; HODAI, Zoltán (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Significant part of the energy need of the world is covered by the use of natural gas. Due to the hydrogen sulphide content of raw gas, the natural gas industry has to tackle some serious problems, for example corrosion-, environmental-, economic- and safety engineering problems. Our aim is to develop the selective hydrogen sulfide absorption by using alkali solutions. Experiments were performed in a specially designed atomizing reactor by using potassium- and sodium hydroxide absorbents. During the tests the following parameters have changed: contact time, pressure, volumetric flow rate of gas and liquid, concentration and material quality of absorbents. Three different model gas mixtures were used for measurements; they consist of nitrogen, carbon dioxide and hydrogen sulfide.